Model of the flux flow losses in a high-temperature superconducting tape exposed to both AC and DC transport currents and magnetic fields. - Schonborg, N.
Recent progress in the high-temperature superconductor technology will probably be of importance for future power applications. In these applications, the power loss is a very important quantity, which has to be described in a relevant manner to obtain an optimum utilization of the conductor. In most power applications the magnitude of the transport current will be quite close to the critical current. In addition to the hysteresis losses, for such high currents, the flux flow losses have to be taken into account. We present a semiempirical model of the flux flow losses in a tape shaped conductor, based on measurements and reasonable physical assumptions. The model gives the flux flow loss as function of temperature, a transport current consisting of both ac and dc components and an applied homogeneous magnetic field with an amplitude proportional to the current.
Keywords: AC magnetic field; AC transport current; DC magnetic field; DC transport current; Flux flow loss; High temperature superconducting tape; Power loss; Semiempirical model